PENGARUH CAR FREE DAY TERHADAP PENGGOLONGAN KUALITAS UDARA PARAMETER SO2 DAN NO2 DI DEPAN MESJID RAYA SUMATERA BARAT KOTA PADANG - Muhamad Ridwan; Charles Situmorang; Hening Darpito (FT-USNI, 2020)
One of the programs of the Padang city government in reducing air pollution is with Car FreeDay program which is held every Sunday which is carried out in front of Mesjid Raya Sumatera Barang,Jalan Khatib Sulaiman, Padang City. In this research was intended to determine the effect of the CarFree Day program on ambient air quality with the parameters: NO2 and SO2. The methodology of thisresearch is to carry out direct measurements using an impinger to measure NO2 and SO2.Measurements were carried out for 2 weeks (Non Car Free Day and Car Free Day), then air qualityclassification was carried out using the Air Pollution Standard Index approach (Pendekatan IndeksStandar Pencemraran Udara, ISPU). The results showed that on Car Free Day (Sunday) for parametersof NO2 reduced NO2 values in the air from 43.25 μg/Nm3 to 7.5 μg/Nm3 and for parameters of SO2 onCar Free Day (Sunday) reduced SO2 values from 47,916 μg/Nm3 to 25.5 μg/Nm3 and for theclassification of air quality using Air Pollution Standard Index approach (Pendekatan Indeks StandarPencemraran Udara, ISPU) shows the air quality in front of the Masjid Raya Sumatera Barat, JalanKhatib Sulaiman, Padang City is good.